Analysis of The Effect of Fabrication and Installation Work on Cost Overruns in Steam Turbine Generator Projects and Coal Boilers in Palembang - Jenni Ria Rajagukguk; Kudus Yallbert (International Journal of Management Science and Information Technology, 2022)
Delays (time overruns, SPI < 1) and exceeding budget costs (cost overruns, CPI < 1) on EPC (Engineering, Procurement, Construction) Projects are a global phenomenon due to the very diverse and unique nature of construction projects so that many companies experience losses during construction execution work activities. A very critical job in the execution of EPC projects is fabrication and installation activities which are part of construction activities because there are very many variables that have an impact on cost overruns if the fabrication and installation work is not monitored and controlled properly.   In this study, an analysis of the effect of fabrication and installation work on cost overruns was carried out on the Steam Turbine Generator and Coal Boiler Project in Palembang.  The analysis was performed using SPSS Ver software. 25 by processing questionnaire data from the answers of 42 respondents. With good control and early anticipation of construction activities so that it can help project managers in managing projects more effectively and efficiently so that the SPI (Schedule Performance Index) and CPI (Cost Performance Index) are more than one and the achievement of other requirements in accordance with project specifications and contracts.